Genetic and and neural predictors of behavioral weight loss treatment: A preliminary study. Issue 1 (2nd November 2016) - Chen, Eunice Y.; Olino, Thomas M.; Conklin, Chris J.; Mohamed, Feroze B.; Hoge, W. Scott; Foster, Gary D.; Arlt, Jean M.; Eneva, Kalina; Kidd, Judy R.; Kidd, Kenneth R.; Lent, Michelle R.; et al.
Abstract : Objective: To examine neural mechanisms of action in behavioral weight loss treatment (BWL) and explore neural and genetic predictors of BWL. Methods: Neural activation to milkshake receipt and genetics were compared in 17 women with obesity who received 12 weeks of BWL and 17 women who received no intervention. Participants were scanned twice using functional magnetic resonance imaging at baseline and 12 weeks. Weight was assessed at baseline, 12, 36, and 60 weeks. Results: BWL participants lost more weight than controls at 12 weeks (−4.82% versus −0.70%). After 12 weeks, BWL had greater reduction in right caudate activation response to milk shake receipt than did controls. Among BWL participants, baseline to 12‐week reduction in frontostriatal activation to milk shake predicted greater weight loss at 12, 36, and 60 weeks. Possessing the A/A or T/A genotype of the fat mass and obesity–associated (FTO) variant rs9939609 predicted greater weight loss at 12 and 36 weeks. Conclusions: These preliminary data reveal that reduction in right caudate activation may be a neural mechanism of weight loss in BWL, and baseline FTO variant and reduction in frontostriatal activation during BWL predict short‐ and long‐term weight loss. These findings require replication in larger samples.